Factors that affect customer satisfaction and brand loyalty for the apple brand in indonesia - Amellia Mel; Margaretha Pink Berlianto (Enrichment : Journal of Management, 2022)
Currently the existing business competition is very tight, so companies are required to continue to maintain their quality and innovate on goods and services. As is the case in the electronic product business, where companies must continue to consider what things can affect customer satisfaction and brand loyalty. In this case, the subjects and objects in this study are brand trust, brand identification, brand experience, location and environment, lifestyle congruence, perceived value of cost, perceived quality that affect customer satisfaction and brand loyalty. This study was shown to determine how big the influence between the dimensions of brand trust, brand identification, brand experience, location and environment, lifestyle congruence, perceived value of cost, perceived quality on customer satisfaction and brand loyalty. This research is causal research using a descriptive quantitative approach. The population used in this study were Apple customers, while the sample taken was 200 people. This research is sourced from primary data obtained through questionnaires. The data analysis technique used in this research is Structural Equation Modeling (SEM) analysis using Partial Least Square (PLS) program. The results of this study indicate that brand experience, location and environment have a positive effect on customer satisfaction, brand identification, brand trust, lifestyle congruence, perceived quality, and perceived value of cost have no effect on customer satisfaction, customer satisfaction has a positive effect on Apple's brand loyalty. The contribution of this research is expected to be a consideration and input for Apple to consider the factors that influence Apple's customer satisfaction and brand loyalty.